Labor Productivity in Hotel Service: Empirical Evidence from Vietnam - Huy, Nguyen Khanh; Linh, Nguyen Khanh (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2021)
Service industries in emerging economies are facing the problem of underrated labor productivity due to difficulties in precise measurement and effective management. Therefore, it is necessary to find solutions to such issues. This study concentrates on popular hotel services in Vietnam which are also encountering challenges in labor productivity management. The data is obtained from the General Statistics Office of Vietnam national census in 2018 on the performance of 1,400 enterprises operating in Vietnam hotel services and presents findings on the determinants of labor productivity. Specifically, labor cost, total capital, before-tax profit, number of rooms, number of room days, and accommodation revenue are among the most-affecting factors. These findings pave the way for further studies to represent a brand-new and more advance measurement for labor productivity, not only for hotel service but also for the service sector in general.